Encountering diversity in Indian biblical studies : a biblical masala - Chalcraft, David J.; Angami, Zhodi (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book provides analysis of a variety of biblical narratives and texts which are the vehicle for the expression, articulation and performance of diverse identities in the Indian context and is the first attempt to do so for a global audience of scholars and students. From pan-Indian social problems attributed to caste, class and gender inequality, to specific North Eastern tribal settings, Dalit struggles in rural Andhra Pradesh, and the experience of Christian autorickshaw drivers in urban Chennai, the book explores the diverse geographical, cultural, social, economic and linguistic settings in which the Bible is encountered. The holistic and multidisciplinary approach to Biblical studies adopted broadens the field beyond textual exegesis. Encounters with the Bible are revealed in diverse chapters impacted by contexts of caste realities, the history of Indian Christianity, colonial and post-colonial frameworks, and educational institutions. Full use is made of 'vernacular' texts and traditions including oral and written cultural, folk tale, literary and auto/biographical narratives in Tribal, Dalit and British colonial settings. Diversity of method is championed through including sociological analysis of Indian social realities, qualitative fieldwork techniques and a kaleidoscope of visual and sensory environments with over 30 photographs. The book celebrates and promotes diversity in Indian biblical studies, creativity and sometimes conflicting perspectives. Encountering Diversity in Indian Biblical Studies will be of interest to students, scholars, and researchers working on postcolonial biblical studies and diversity in Christianity, particularly in the Indian context"--
Keywords: Bible -- Hermeneutics; Christianity -- India; Group identity -- India; India -- Church history; RELIGION / Bible / Criticism, Interpretation / Old Testament; RELIGION / Bible / Criticism, Interpretation / New Testament; RELIGION / Bible / General